Pembuatan Sabun Transparan dengan Penambahan Ekstrak Kayu Secang (Caesalpinia Sappan L) Sebagai Antibakteri - DIAN, Dian Ayu Lailatul Fitriyah; Adinda Putri Rachmawati; Titi Susilowati Kindriari Nurma Wahyuni; Nana Dyah Siswati (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Secang Sappanwood grows wild in tropical areas and has a main content of brazilin, which is approximately 200 mg/g. Brazilin is reported to have biological activities such as antibacterial, anti-inflammatory, anti-allergic, antioxidant, and anti-acne. This research aims to obtain transparent soap with secang wood extract which has the best inhibition zone for P. Acnes bacteria and the quality of the soap is in accordance with the SNI standard. The test was carried out using the disc diffusion method. It was started by making Sappanwood extract, then making transparent soap with Sappanwood extract at concentrations of 0.5%, 0.75%, 1%, 1.25%, and 1.5% (w/v). Moreover, it was followed by an antibacterial test of transparent soap. Based on the GC-MS analysis, there was a content of fatty acid of 53.53%, phenolic compound of 25.26%, and terpenoid compound of 6.53%. The results of the organoleptic test on transparent solid soap from Sappanwood extract were reddish-yellowish to reddish brownies with a solid texture and a distinctive oil aroma. It also had a pH of 9.54, water content of 10.8%, and free alkali of 0.072%, which met the SNI quality standards. This soap also had an inhibition zone of 14 mm with the best concentration of 1.5%.